Marriage impediment in the Polish Family and Guardianship Code - KOSEK, MIROSŁAW (Prawo Kanoniczne, 2012)
The article is an extended version of the study presented during a scientific conference organized by the Faculty of Canon Law of Cardinal Stefan Wyszynski University in Warsaw on 25th April 2012 dedicated to marriage impediments under Polish law and Canon law. The article contains a study of the provisions of the Family and Guardianship Code regulating impediments to marriage. The first part presents the very beginning of the provisions in that matter under Polish law and a list of different types of impediments to marriage. The second part embraces a specific description of the types of impediments to marriage with special regard to the full legal incapacitation and mental illness or retardation impediment. The article does not cover the age impediment (Art. 10 of the Family and Guardianship Code) since it was the subject of a separate study at the above-mentioned conference.